Tuez les Tous! Rwanda: Histoire du Genocide . Rwanda: History of Genocide - Hazan, David; Glucksmann, Raphaël; Mezerette, Pierre (Hazanavicius, Michel ; Borg, Arnaud, 2004)
Duration: 01:37:00 One of the darkest and most under-reported tragedies of the 20th century gets near-definitive treatment in "Rwanda: History of a Genocide." At once coolly dispassionate and emotionally overpowering, this engrossing French documentary narrates in straightforward fashion events leading up to the April 1994 massacres, implicating Western imperialism for its role in inflaming and encouraging the massacres. The film argues persuasively that what was strictly a class divide between the nation's Hutu majority and elite Tutsi minority became a racial conflict only after German colonists arrived on the scene in the late 1800s. The narrative sweeps across 100 years of history to the early 1990s, with the Hutus (or "true Rwandans," as they call themselves) locked in a civil war with the Rwandan Patriotic Front, a paramilitary organization of exiled Tutsis attacking from the outside.The film's most impressive achievement is the clarity with which it maps out the frenzied yet disquietingly robotic machinery of the genocide, from the birth of the extremist group Hutu Power to the chilling radio messages, eerily played over placid nighttime shots of the Rwandan capital of Kigali, urging Hutus to kill the "Tutsi cockroaches." Footage of the actual massacres -- of corpses piled by the hundreds on roads, in ditches and, in one surreal shocking image, floating down river -- is deployed sparely and brutally effective.Even when focusing on individual survival stories, moments that could potentially sink into bathos or exploitation, Glucksmann, Mezerette and Hazan seek out deeper, more complex truths.